Factors affecting the USD/VND exchange rate : Luận văn ThS. Kinh doanh: 603401 - Nguyen, Thi Thuy Linh (2019)
The study presents an overview of USD/VND exchange rate in Vietnam, a theoretical framework, and a review of the literature on the theme of factors affecting the exchange rate. From those, the author chose some macroeconomic variables which were divided into two groups to find the better performance group of variables in explaining the USD/VND exchange rate. The research used Johansen Cointegration Tests to investigate the long-run relationship between the variables, then led to use the Vector Error Correction Model (VECM) to estimate the equation of the exchange rate. The main findings of the thesis are: 1) In the short-run horizon, only Interest Rate does Granger cause the Exchange rate at the level of 10% significance. And there are five cointegrating relations between six variables, mean existing five long-run relationships between variables according to Johansen Cointegration Tests result; 2) Excluding the historical Exchange Rate, the two main variables affecting the Exchange Rate are GDP and Balance of Payment – current account, however, the proportion of each variables changing over time in Variance Decomposition analysis. 3) Conventionally, the Interest Rate and Reserves are usually used as tools of the Exchange Rate intervention of the government, however, both appear to play a small role in affecting the Exchange Rate in short-term horizon. 4) The Inflation and Interest Rate in the model can give better performance (with higher adjusted R2) than the differentials of Inflation and Interest Rate between Vietnam and the US. Those results emphasize some implications for the policymaker, organizations as well as encourage for further study in USD/VND exchange rate, for example, in a larger sample, and in forecasting. Keywords: USD/VND exchange rate, factors affecting, VECM, macroeconomic factors, GDP, BOP, Inflation, policy-maker.